2020
DOI: 10.1016/j.chembiol.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI5P4K Lipid Kinase Family in Cancer Using Covalent Inhibitors

Abstract: Highlights d Inhibitor THZ-P1-2 shows PI5P4K enzyme inhibition and target engagement in cells d THZ-P1-2 covalently targets unannotated cysteines outside the PI5P4K active site d AML/ALL cell lines are broadly sensitive to THZ-P1-2's covalent effects d PI5P4K inhibition causes autophagy disruption and upregulates TFEB signaling

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…All things considered, in the recent past, PI5P4Ks and their product PI-4,5-P 2 have risen from insignificance to being without a doubt one of the key metabolic sensors and regulators within the cell as well as pivotal players for interorganelle communication necessary for cell survival. With drugs being developed against these kinases (Davis et al, 2013;Clarke et al, 2015;Al-Ramahi et al, 2017;Kitagawa et al, 2017;Manz et al, 2020;Sivakumaren et al, 2020;Chen et al, 2021), targeting them in the near future in various diseases is looking brighter.…”
Section: Health and Disease: Pi5p4ks Emerge As Exciting Targetsmentioning
confidence: 99%
“…PIP4K2A is a member of the phosphatidylinositol-5-phosphate 4-kinase family and mediates secretion, cell proliferation, differentiation, and motility ( Rameh et al, 1997 ). It is associated with cancer ( Sivakumaren et al, 2020 ) and it has also been examined for potential involvement in schizophrenia, but only a minor association was reported ( Thiselton et al, 2010 ). PIP4K2A rs10828317, rs746203, and rs8341 have been investigated for potential association with TD in a cohort of 491 patients of Siberian origin, but only rs10828317 was associated with TD development ( Fedorenko et al, 2014 ).…”
Section: Pharmacogenomic Studies Focusing On the Association Between Tardive Dyskinesia And Genes Involved In The Pharmacodynamicsmentioning
confidence: 99%